Estimation of the share of artificial Po-210 contamination in the ambient air - Magdalena Długosz-Lisiecka; Karolina Nowak (Archives of Environmental Protection, 2021)
In this work, source apportionment for unsupported 210Po was conducted. The activity size distributions of both supported and unsupported 210Po in urban aerosols were measured from February to December 2019. The results confirmed that the activity of 210Po in the atmosphere is significantly increased by additional 210Po content related to coal combustion by-product releases, especially in the cold winter season. The sources of this content are local emissions and long-range transport processes. Unsupported activity concentrations of 210Po and weather parameters (temperature, humidity, and wind velocity) were used for source apportionment from three heating systems.